Long-Term Survival Following Pancreatectomy and S-1 Chemotherapy for Pancreatic Acinar Cell Carcinoma With Peritoneal Dissemination. Issue 1 (January 2015) - Sumiyoshi, Tatsuaki; Shima, Yasuo; Okabayashi, Takehiro; Kozuki, Akihito; Iwata, Jun; Saisaka, Yuichi; Tokumaru, Teppei; Nakamura, Toshio; Morita, Sojiro; Gumaste., Vivek
<x xml:space="preserve">Abstract</x> Abstract Current case is the third report of S-1 chemotherapy against acinar cell carcinoma (ACC) of pancreas, and our patient has achieved the longest reported recurrence-free survival, longer than 6 years, despite the presence of disseminated nodules at laparotomy. A 77-year-old man presented with abdominal discomfort. Computed tomography showed a low-density tumor in the pancreas tail and the patient was referred for surgery. A 3-cm sized pancreatic tumor, with localized disseminated nodules, was detected on laparotomy. Distal pancreatectomy with concomitant resection of disseminated nodules was performed, and histopathological examination revealed an ACC. Oral S-1 chemotherapy was administered postsurgery, and the patient showed no sign of recurrence during 73 months of follow-up. This is the first report of long-term survivor of pancreatic ACC with peritoneal dissemination, following pancreatectomy and S-1 chemotherapy. Current case suggests a beneficial effect of S-1 chemotherapy in cases of ACC.